2014
DOI: 10.1038/nature13592
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt glacial climate shifts controlled by ice sheet changes

Abstract: During glacial periods of the Late Pleistocene, an abundance of proxy data demonstrates the existence of large and repeated millennial-scale warming episodes, known as Dansgaard-Oeschger (DO) events. This ubiquitous feature of rapid glacial climate change can be extended back as far as 800,000 years before present (BP) in the ice core record, and has drawn broad attention within the science and policy-making communities alike. Many studies have been dedicated to investigating the underlying causes of these cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
223
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(241 citation statements)
references
References 97 publications
14
223
4
Order By: Relevance
“…These results are broadly consistent with previous research (e.g. Zhang et al, 2014Zhang et al, , 2017, but the timing and duration of the most sensitive interval of time and the likelihood that a forcing produces a longer-term cooling event may ultimately depend on a complex interplay between ice volume and atmospheric CO 2 (Zhang et al, 2017). Atmospheric pCO 2 during the YD initiation was relatively high (∼ 240 ppmv) and could therefore affect the timing of ideal conditions for abrupt climate change in conjunction with ice volume, but their precise interdependence is still unclear.…”
Section: Sensitivity To Ice Volumesupporting
confidence: 83%
See 1 more Smart Citation
“…These results are broadly consistent with previous research (e.g. Zhang et al, 2014Zhang et al, , 2017, but the timing and duration of the most sensitive interval of time and the likelihood that a forcing produces a longer-term cooling event may ultimately depend on a complex interplay between ice volume and atmospheric CO 2 (Zhang et al, 2017). Atmospheric pCO 2 during the YD initiation was relatively high (∼ 240 ppmv) and could therefore affect the timing of ideal conditions for abrupt climate change in conjunction with ice volume, but their precise interdependence is still unclear.…”
Section: Sensitivity To Ice Volumesupporting
confidence: 83%
“…Zhang et al, 2014Zhang et al, , 2017, and here we investigate this further by examining the timing of Greenland stadials relative to ice volume (estimated using Red Sea sea level; Siddall et al, 2003). The timings of 55 stadial initiations as compiled in the INTIMATE (INTegration of Ice core, MArine, and TErrestrial) initiative (Rasmussen et al, 2014) are compared relative to ice volume, and indeed a strong bias towards intermediate ice volume conditions exists, with 73 % of the millennial-scale cooling events occurring during only 40 % of the range of sea level across the interval from 0 to 120 ka BP (Fig.…”
Section: Sensitivity To Ice Volumementioning
confidence: 99%
“…This echoes the results of experiment TOP that suggested that any change in the heat transported by the AMOC is but one constituent of the heat transported by the ocean and that changes in the shallow, wind-driven circulation are equally important. Zhang et al (2014) also found a dramatic increase in the AMOC in their model simulations of a White Mountain, but they did not report how the equatorial heat transport was different. We will note that a very much stronger AMOC is not a consistent feature of White Mountain simulations: other simulations of HadCM3 with the same height of ice sheet but using a land-sea mask of the LGM, rather than the preindustrial that we show here, do not show a large increase in their AMOC.…”
Section: Alb/topmentioning
confidence: 92%
“…With aid of the comprehensive coupled climate model COSMOS 8,9 we explore the governing mechanism of AMOC stability associated with atmospheric CO 2 changes. Two experiments were conducted with gradual changes in atmospheric CO 2 under intermediate (CO2_Hys) and maximum (LGM_0.15_CO2) ice volumes (Supplementary Table 1 Supplementary Fig.…”
Section: Gradual Co 2 Changes As a Forcing Factormentioning
confidence: 99%